2021
DOI: 10.1038/s41467-021-27121-x
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed electronic contribution in thermal conductivity of Ge2Sb2Se4Te

Abstract: Integrated nanophotonics is an emerging research direction that has attracted great interests for technologies ranging from classical to quantum computing. One of the key-components in the development of nanophotonic circuits is the phase-change unit that undergoes a solid-state phase transformation upon thermal excitation. The quaternary alloy, Ge2Sb2Se4Te, is one of the most promising material candidates for application in photonic circuits due to its broadband transparency and large optical contrast in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…[ 32 ] The thermal conductivity of the PCM layer, denoted as κ ( T ), was assumed to vary with temperature based on ref. [53], while the remaining material properties for the simulated non‐PCM layers were considered to be temperature‐independent as presented in Table 1 .…”
Section: Device Configuration and Thermal Modelingmentioning
confidence: 99%
“…[ 32 ] The thermal conductivity of the PCM layer, denoted as κ ( T ), was assumed to vary with temperature based on ref. [53], while the remaining material properties for the simulated non‐PCM layers were considered to be temperature‐independent as presented in Table 1 .…”
Section: Device Configuration and Thermal Modelingmentioning
confidence: 99%
“…The ability to change the thermal conductivity (k) of a material "on-demand" has gained significant traction in recent years, with research efforts focused on materials and mechanisms that enable large on/off switching ratios (k high / k low ), fast modulation between the two states (<seconds), and trigger mechanisms that can be easily accessed in solid-state architectures (e.g., no moving parts). With developments in materials science and thermometry techniques, several material systems have been discovered with thermal-switching behavior under different stimuli such as electrical 9 , thermal 10 , electrochemical 11,12 , optical 13 , magnetic 14 , strain 15 , and even hydration 16 . Although some of these materials provide large switching ratios (up to an order of magnitude), their complicated trigger mechanisms and the associated switching timescale limit their applications.…”
mentioning
confidence: 99%
“…One possible solution to address this issue is to use a new class of PCMs, called GSST. GSST, which has been studied for PCM-based photonic applications, shows superior performance in terms of thermal stability-through doping Se atoms and excess Ge atoms, which leads to an increase of the T g [42], [122], [123]-and lower material loss contrast compared to GST (because of lower κ) [34], [122], [123]. The work in [21] suggested that different figures of merits (FOMs) of FOM 1 = n/ κ a and FOM 2 = n/ κ c can be used to quantify the performance of OPCMs.…”
Section: Loss and Crosstalk Noisementioning
confidence: 99%
“…The work in [36] presented analytical models for thermo-optic coefficient of GST. The presented models can be used to further optimize the performance of GST-based OPCM cells [34], [36]. In addition, the work in [124] presented an experimental study on the impact of temperature variation and transmission drift in OPCMs employed for in-memory computing units.…”
Section: E Thermal Sensitivitymentioning
confidence: 99%